Biological activities of quercetin and other flavonols: A mini-review - SILVA, Edson Pablo; HERMINO, Vanessa Leal de Queiroz; RODRIGUES, Leticia; BARBOSA, Josiane; FREITAS, Flávio Augusto de; SOUZA, Cesar; CARVALHO, Rosany Piccolotto; MADURO, Isolda Prado de Negreiros Nogueira; MACAMBIRA, Simone Garcia; SOARES, Milena (Food Science and Technology, 2024)
There are countless benefits arising from the consumption of vegetables, which can present significant levels of compounds with bioactive properties, effectively acting in the promotion of human health. Bioactive compounds that play an antioxidant role have been widely studied since most of the diseases that affect humans can be derived from the presence of free radicals in the body, leading to a series of metabolic disorders. Quercetin has several pharmacological activities and antioxidant, anti-inflammatory, vasodilator, and anticancer effects. Despite the efficacy and safety of its consumption, the limited bioavailability of this phenol continues to be highlighted as a main concern, where factors such as solubility, absorption, and metabolism have a direct influence on this process and its beneficial effects. Among the compounds with antioxidant activity are flavonoids, such as quercetin, which have shown great effectiveness and are even associated with very positive responses against some types of tumor cells. Quercetin is shown to be a powerful ally in promoting health and a better quality of life. However, further studies are needed to be able to accurately state the benefits resulting from the consumption of this compound.